Incidental Capture and Mortality of Olive Ridley Turtles (Lepidochelys olivacea) in Commercial Trawl Fisheries in Coastal Waters of Orissa, India - Gopi, G. V.; Pandav, B.; Choudhury, B. C. (Chelonian conservation and biology, 2006)
A shrimp trawl fishery study was conducted in the coastal waters of Orissa, India, from November 2001 to March 2002; 76 trawls in water of 6–35 fathoms resulted in the capture of 26 olive ridley turtles (Lepidochelys olivacea). Most turtle captures occurred within 5 km of the shoreline and at a depth of less than 10 fathoms, emphasizing the need for greater protection of these nearshore habitats. Data revealed a strong relationship between tow time and mortality of turtles.